Sorption mechanism, hygroscopic agents, and application of passive water evaporative cooling technology—A review - Pei-Xia Qi; Jun-Ji Xu; Hong-Ya Li; Ji-Peng Luo; Quan Shi (Chemical Thermodynamics and Thermal Analysis, 2025)
Passive water evaporative cooling technology (PWECT) is an efficient cooling technology that can provide unparalleled cooling capacities compared to other passive technologies. Hygroscopic agents are essential to PWECT since they absorb external water vapor to guarantee a stable supply of liquid water for evaporative cooling. Compared with previous reviews that only focused on a single type of sorbent, this review provides a detailed analysis of multiple types of single sorbents and composite materials. In the first section of this review, the basic sorption theory, including sorption mechanism, sorption kinetics, and sorption thermodynamics, is reviewed. Subsequently, the hygroscopic characteristics, preparation methods, and application fields of sorbent materials are studied in depth in order to better select and design materials appropriate for various application scenarios. The last section summarizes the latest research progress on hygroscopic materials and PWECT applications and provides an outlook on the future development of PWECT systems.